Beekeeping in late medieval Europe: A survey of its ecological settings and social impacts - Lluis Sales Fava; Alexandra Sapoznik; Mark Whelan (Anales de la Universidad de Alicante. Historia Medieval, 2021)
In the middle ages bees held significant economic, social and cultural importance. Constant demand for wax was driven by Christian religious practice among many other uses, while honey provided the only widely accessible sweetener in an era before large-scale sugar imports. Consequently, beekeeping was a notable part of the rural economy, drawing on the participation of numerous groups across Europe, from peasants with only a few hives for small-scale production to specialized beekeepers producing for a thriving international trade. Analysis of a wide variety of documents from northern and southern Europe, shows the importance of beekeeping in the late medieval period, and the ways in which different environments and types of economic and social organization consequently gave rise to different forms of beekeeping. This paper demonstrates that beekeeping was not an isolated activity, but rather one which competed and conflicted with, and conflicted with, many other types of resource use from a variety of actors. As such, beekeeping provides a lens through which to consider human intervention in the natural environment, demonstrating the extent to which the medieval landscape was regulated, managed, mediated and anthropized.